2007
DOI: 10.2478/s11686-007-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Oxyascaris (Nematoda, Cosmocercidae) in the Costa Rica brook frog, Duellmanohyla uranochroa (Anura, Hylidae)

Abstract: Oxyascaris mcdiarmidi sp. nov. (Nematoda, Cosmocercidae) from the small intestine of Duellmanohyla uranochroa from Costa Rica is described. Oxyascaris mcdiarmidi sp. nov. represents the 4th species assigned to the genus and is distinguished from congeners by the distribution pattern of the caudal papillae of the male, spicule length and vulvar position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Oxyascaris oxyascaris was initially described parasitizing the snake Mastigodryas bifossatus Raddi, 1820 (= Drymobius bifossatus ) in Rio de Janeiro (Vicente et al, 1991). Currently, the genus is composed of four other Oxyascaris species: Oxyascaris similis Travassos, 1920 (= Pteroxyascaris similis ), Oxyascaris caudacutus Freitas, 1958, Oxyascaris mcdiarmidi Bursey and Goldberg, 2007 (Bursey & Goldberg, 2007). In Brazil, there are records of O. oxyascaris infecting amphibians of the Leptodactylidae family in the South and Southeast regions (Vicente et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxyascaris oxyascaris was initially described parasitizing the snake Mastigodryas bifossatus Raddi, 1820 (= Drymobius bifossatus ) in Rio de Janeiro (Vicente et al, 1991). Currently, the genus is composed of four other Oxyascaris species: Oxyascaris similis Travassos, 1920 (= Pteroxyascaris similis ), Oxyascaris caudacutus Freitas, 1958, Oxyascaris mcdiarmidi Bursey and Goldberg, 2007 (Bursey & Goldberg, 2007). In Brazil, there are records of O. oxyascaris infecting amphibians of the Leptodactylidae family in the South and Southeast regions (Vicente et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation that justifies the low values of the parasitological descriptors for these genera recorded in this work is the sample effort, which was important to reveal rare species associated with this host. These parasite larvae can be found infecting amphibians that act as second intermediate or paratenic hosts (Sprent, 1979; Vicente et al, 1993; Moravec et al, 1997; Goldberg & Bursey, 2007; Goldberg et al, 2009 and González & Hamann, 2013). The precise identification of these helminths was not possible because only one specimen of each was found.…”
Section: Discussionmentioning
confidence: 99%
“…Oxyascaris mcdiarmidi was described from Duellmanohyla uranochroa from Costa Rica by Bursey and Goldberg (2007a). It also occurs in a brachycephalid frog, Craugastor ranoides from Costa Rica (Goldberg and Bursey 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al (2006) listed platyhelminth parasites from 6 Costa Rican hylid species, Isthmohyla lancasteri, Scinax boulengeri, Smilisca baudinii, Smilisca phaeota, Smilisca puma and Trachycephalus venulosus. As part of an ongoing series of studies on this subject (Bursey and Goldberg 2005, 2006, 2007a,b, Bursey et al 2001, Goldberg and Bursey 2008 reported helminths from an additional 18 anuran species from Costa Rica. Although some 133 anuran species are thought to occur in Costa Rica (Savage 2002), there are helminth records for only approximately one quarter of them.…”
Section: Introductionmentioning
confidence: 99%
“…Oxyascaris oxyascaris was described for the first time in reptiles (Travassos 1920), and then a new species, O. necopinus (sinonym of O. oxyascaris -Baker andVaucher 1985, Bursey andGoldberg 2007), was proposed by Freitas (1958) for specimens found in the small intestine of the frogs Leptodactylus ocellatus, L. sibilatrix and Pleuroderma diplolistris. This species was found with low prevalence at REGUA and was not recorded at EEEP.…”
Section: Discussionmentioning
confidence: 99%